2017
DOI: 10.1097/adm.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Use of Smoking Cessation Methods Among Patients Receiving Office-based Buprenorphine Maintenance Treatment

Abstract: Objectives Provision of smoking cessation treatment is limited in office-based buprenorphine maintenance treatment (BMT) settings. This study describes smoking and smoking cessation behaviors among patients receiving office-based BMT. Methods Cross-sectional study of patients receiving office-based BMT at a community health center in the Bronx, NY. We interviewed patients assessing sociodemographic, substance use and tobacco use characteristics, including methods used for smoking cessation. We report simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…In line with our findings, evidence from data published prior to the pandemic suggest that most people with OUD who smoke are motivated to quit and try to quit (See Vlad et al, 2020 for a review; Shah et al, 2017 ). For example, Nahvi and colleagues (2006) conducted a cross-sectional survey study of patients in methadone treatment and reported about half (48%) of smokers were contemplating quitting smoking.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our findings, evidence from data published prior to the pandemic suggest that most people with OUD who smoke are motivated to quit and try to quit (See Vlad et al, 2020 for a review; Shah et al, 2017 ). For example, Nahvi and colleagues (2006) conducted a cross-sectional survey study of patients in methadone treatment and reported about half (48%) of smokers were contemplating quitting smoking.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings apply to patients with OUD who were stable in office-based buprenorphine treatment at the start of a COVID-19 surge and may not generalize to individuals who smoke cigarettes or vape nicotine and are in other OUD treatment programs (e.g., methadone maintenance) or to less stable samples such as those out of treatment and actively using opioids. The survey response rate may have been higher had we been able to approach patients in-person at their regular office visits as originally planned, as this has been shown to optimize response rates in other vulnerable samples ( Oga et al, 2018 ; Shah et al, 2017 ). This strategy was precluded by restrictions on research recruitment during the COVID-19 surge at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, two out of the seven participants who completed the GFAQ reported switching entirely from conventional cigarettes to electronic cigarettes at the 6-month session. This is in accordance with previous research among clients with SUDs who were engaged in medication-assisted treatment: 15% of clients who were current smokers had used electronic cigarettes as part of a smoking cessation attempt (Shah, Cunningham, Brisbane, DeLuca, & Nahvi, 2017). Oncken and colleagues (2017) reported that a history of substance abuse was associated with electronic cigarette use during pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…A vast majority (75%) of individuals included in our study were daily smokers, compared to an average of 9% in the general adult Swedish population [24]. International research on substance dependence shows tobacco smoking prevalence in 73-97%, with OST patients generally being at the higher end [2533]. Apart from tobacco smoking, inhalation, smoking, or intravenous use of substances can cause a wide spectrum of diseases affecting the lungs, either direct or indirect.…”
Section: Discussionmentioning
confidence: 99%